Planering och anläggning av en uteplats i parhusområde - Nilsson, Lars (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
In a condominium with two-apartment buildings, lies an area, formerly used as a playground, nowadays wasted and abandoned. The owner wanted to embellish the place and get a new use for it, preferably as a gathering- and feast-place. The work is described with focus on the construction with describing pictures and sketches. The production of the sketches is not reported more than that they are attached at the end of the paper. The practical work is done and documented. The texts and pictures describe the work step-by-step. The result of the project is an enhanced living-area in which the tenants can be comfortable and associate more. From the owner's point of view, the apartments will be more attractive to the market as the surroundings are more beautiful.